Life Course Socioeconomic Status and Hypertension in African American Adults: The Jackson Heart Study. (16th August 2019) - Glover, Láshauntá M; Cain-Shields, Loretta R; Wyatt, Sharon B; Gebreab, Samson Y; Diez-Roux, Ana V; Sims, Mario
Abstract: BACKGROUND: Limited research has examined the association of life-course socioeconomic status (SES) with hypertension prevalence and incidence in a large cohort of African Americans. METHODS: Among 4, 761 participants from the Jackson Heart Study (JHS), we examined the association of SES indicators with prevalent and incident hypertension. We used multivariable Poisson regression to estimate prevalence ratios (PR, 95% confidence interval—CI) of baseline (2000–2004) hypertension by adult (education, income, occupation, wealth) and childhood (mother's education) SES. Cox proportional hazards regression was used to estimate hazard ratios (HR, 95% CI) of incident hypertension by adult and childhood SES (2005–2013; 7.21 median years of follow-up). We also examined the association of childhood-to-adult SES mobility (parent-to-adult education) with prevalent and incident hypertension. Model 1 adjusted for age and sex. Model 2 added waist circumference, behaviors (smoking, alcohol, physical activity, diet), and diabetes prevalence. RESULTS: High (vs. low) adult SES measures were associated with a lower prevalence of hypertension, with the exception of having a college degree and upper-middle income (PR: 1.04, 95% CI: 1.01, 1.07; PR: 1.05, 95% CI: 1.01, 1.09, respectively). Higher childhood SES was associated with a lower prevalence and risk of hypertension (PR: 0.83, 95%: CI 0.75, 0.91; HR: 0.76, 95% CI: 0.65, 0.89, respectively). Upward mobility and consistent high SES (vs. consistent low SES) from childhood to adulthood was associated with a greater prevalence, but lower incidence of hypertension. CONCLUSION: Efforts to prevent hypertension among African Americans should consider childhood and current SES status.